Incidence of non biliary non alcoholic acute pancreatitis in a tertiary hospital (Journal of Surgical Sciences, 2020)
Background: Acute pancreatitis is an important cause of hospital admission with acute abdomen. It is responsible for significant morbidity and also mortality in patients.Objective: To determine the incidence of non-biliary nonalcoholic acute pancreatitis (Non A non B) and also to compare the incidence with alcoholic and biliary pancreatitis in the department of surgery of Chittagong Medical College Hospital, Bangladesh as well as with the developed countriesMethods: This prospective study was carried on 75 patients of both sex having acute abdominal pain characteristic of acute pancreatitis and serum amylase >3 times normal, admitted in General Surgery wards in CMCH and supported by biochemical test during June 2008 to May 2010.Results: The mean (±SD) age was 36.1±15.4 years and 32.7±14.3 years in male and female group respectively (p>0.05) and maximum number was found in the age group of 20-30 years in both groups. Choledocolithiasis were 2(33.3%) and 7(21.9%) in male and female respectively evaluated by USG. Sludge in GB 1(16. 7%) in male and 7(21.9%) in female. Biliary ascariasis 3(50.0%) and 16(50.0%) in male and female respectively. Alcoholic was found 4(16.0%), Biliary 2(8.0%) and Non Alcoholic non Biliary 19(78.0%) in male patients. Biliary 32 (64.0%) and Non Alcoholic non Biliary 18(36.0%) in female patients. The difference was statistically significant (p